Navigating Industrial Action: The Guidance for Medical Students During Resident Doctor Strikes in England [version 2; peer review: 2 approved, 1 approved with reservations] - Hannah Okechukwu; Shonnelly Novintan (MedEdPublish)
Objectives The British Medical Association announced a successful vote towards industrial action to achieve ‘pay restoration’ on 20 February 2023; with 11 walkout periods occurring in the following months. During industrial action, concerns arose about the role medical students would play and the pressure placed upon them to ‘act up’. The objective of this study was to assess the guidance issued by medical schools and local placement sites during industrial action. Design, setting and participants This cross-sectional study collected online survey data between 7 March 2023 and 7 April 2023 from medical students across England. Main outcome measures Reports about guidance issued by medical schools and hospital placements. Results 62% of the medical schools issued guidance stating they were not cancelling clinical placements; of these, 10% said attendance was a personal choice. 17% of medical schools cancelled all clinical placements and 7% did not issue guidance. 52% of medical schools monitored attendance on strike days. 1 medical school and 3 clinical placement sites advertised paid work for students during the industrial action. Conclusion The impact industrial action has on medical students has not been examined. Our results show mixed guidance from medical schools that can contradict local placement guidance. This lack of guidance is mirrored in the existing, yet limited, literature. If students feel pressured to perform tasks outside their remit, with inadequate supervision, it can impact patient safety and their license to practice. For the safeguarding of patients, and students, further work is needed to produce standardised guidance during industrial action.